2006
DOI: 10.1002/cne.20950
|View full text |Cite
|
Sign up to set email alerts
|

GABAB receptors in the centromedian/parafascicular thalamic nuclear complex: An ultrastructural analysis of GABABR1 and GABABR2 in the monkey thalamus

Abstract: Strong gamma-aminobutyric acid type B (GABA(B)) receptor binding has been shown throughout the thalamus, but the distribution of the two GABA(B) receptor subunits, GABA(B) receptor subunit 1 (GABA(B)R1) and GABA(B) receptor subunit 2 (GABA(B)R2), remains poorly characterized. In primates, the caudal intralaminar nuclei, centromedian and parafascicular (CM/PF), are an integral part of basal ganglia circuits and a main source of inputs to the striatum. In this study, we analyzed the subcellular and subsynaptic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 141 publications
(236 reference statements)
4
14
0
Order By: Relevance
“…GABA B R 1a/b IR was in the axolemma as well as in microtubules of both myelinated and unmyelinated axons. These data are in line with previous EM studies of the monkey centromedian/ parafascicular thalamic complex (Villalba et al, 2006), where small axon-like processes were immunopositive for GABA B receptors, and suggest that like other receptor types, receptors after synthesis in cell bodies are transported intraaxonally to insertion into synaptic terminals, where they serve as presynaptic receptors (Herkenham, 1987). Another possibility is that GABA B receptors, as proposed for other receptor types, could be functional receptors modulating axon physiology, influencing axonal conduction and neurotransmitter release (Swanson et al, 1998;Capogna, 2004;Poisik et al, 2005).…”
Section: Electron Microscopysupporting
confidence: 93%
“…GABA B R 1a/b IR was in the axolemma as well as in microtubules of both myelinated and unmyelinated axons. These data are in line with previous EM studies of the monkey centromedian/ parafascicular thalamic complex (Villalba et al, 2006), where small axon-like processes were immunopositive for GABA B receptors, and suggest that like other receptor types, receptors after synthesis in cell bodies are transported intraaxonally to insertion into synaptic terminals, where they serve as presynaptic receptors (Herkenham, 1987). Another possibility is that GABA B receptors, as proposed for other receptor types, could be functional receptors modulating axon physiology, influencing axonal conduction and neurotransmitter release (Swanson et al, 1998;Capogna, 2004;Poisik et al, 2005).…”
Section: Electron Microscopysupporting
confidence: 93%
“…This pattern suggests that R7-Gβ5-R7BP complexes could have different roles in striatum vs. thalamus, which express various Gi/o-coupled receptors pre-or post-synaptically , Galvan et al, 2006, Villalba et al, 2006. The mechanisms that determine the differential targeting of R7BP to certain axons, dendrites or spines remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Knowing that striatal spines display a significant level of neurochemical specificity and receive glutamatergic inputs from different sources (Lei et al, 2004, Raju et al, 2006, we assessed the degree of heterogeneity of R7BP expression associated with striatal spines through quantitative analysis of the relative percentages of immunoreactive and non-immunoreactive spine heads in the rat caudate-putamen complex. The analysis of 521 spines in striatal tissue from three rats revealed that 46% of striatal spines displayed R7BP immunoreactivity, while 54% were non-immunoreactive.…”
Section: Analysis Of R7bp Localization By Immunoelectron Microscopymentioning
confidence: 99%
“…The borders between the basal ganglia-and cerebellar-receiving territories of the ventral motor nuclei were delineated using adjacent Nissl-stained sections (1 section out of 6) combined with drawings of corresponding levels from two rhesus monkey brain stereotaxic atlases (Lanciego and Vazquez 2012;Paxinos et al 1999). In addition, one out of six sections was immunostained for the vesicular glutamate transporter 2 to confirm further the border of the cerebellar-receiving region of the ventrolateral nucleus of the thalamus (Kuramoto et al 2011;Villalba et al 2006). As controls, sections of the thalamus adjacent to those processed to localize Ca v 3.1 immunoreactivity were incubated in solutions, in which the primary MAb were replaced by nonimmune mouse serum.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…The immunoreactive elements were classified based on ultrastructural features (Peters et al 1991), and the relative distribution of Ca v 3.1 immunoreactivity amongst neuronal elements was then statistically compared between normal and MPTP-treated animals using a Mann-Whitney test. Labeled dendrites were divided into small (Ͻ0.5 m), medium (0.5-1 m), or large (Ͼ1 m) profiles, based on their cross-sectional diameter (Galvan et al 2014;Gonzales et al 2013;Villalba et al 2006). The immunogold-stained sections were used to confirm expression of Ca v 3.1 labeling on the plasma membrane and at synaptic sites along immunoreactive dendrites.…”
Section: Immunohistochemistrymentioning
confidence: 99%